2014
DOI: 10.1155/2014/762570
|View full text |Cite
|
Sign up to set email alerts
|

The Study of the Frequency Effect of Dynamic Compressive Loading on Primary Articular Chondrocyte Functions Using a Microcell Culture System

Abstract: Compressive stimulation can modulate articular chondrocyte functions. Nevertheless, the relevant studies are not comprehensive. This is primarily due to the lack of cell culture apparatuses capable of conducting the experiments in a high throughput, precise, and cost-effective manner. To address the issue, we demonstrated the use of a perfusion microcell culture system to investigate the stimulating frequency (0.5, 1.0, and 2.0 Hz) effect of compressive loading (20% and 40% strain) on the functions of articula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…72 In addition, chondrocytes in monolayer stimulated with 20% compressive strain at 2 Hz exhibited an estimated 45% upregulation of GAG production. 36 These studies along with others shown in Table 1 confirm the benefits that DC stimulation has on GAG content in AC constructs. 8,11 Shear AC experiences shear stresses during normal physiological movement and loading.…”
Section: Direct Compressionsupporting
confidence: 69%
See 1 more Smart Citation
“…72 In addition, chondrocytes in monolayer stimulated with 20% compressive strain at 2 Hz exhibited an estimated 45% upregulation of GAG production. 36 These studies along with others shown in Table 1 confirm the benefits that DC stimulation has on GAG content in AC constructs. 8,11 Shear AC experiences shear stresses during normal physiological movement and loading.…”
Section: Direct Compressionsupporting
confidence: 69%
“…In static cultures, chondrocytes in the inner region of AC constructs have limited access to signals and nutrients causing them to lose function and their chondrocytic phenotype. 36 Cell viability and proliferation are measured using metabolic assays, and cellular content may be measured indirectly by quantifying DNA content. TEAC is biomimetic and employable for translation only if it houses viable chondrocytes with high proliferative potential and AC-specific ECM production.…”
Section: Cellular Performancementioning
confidence: 99%
“…Active fetal movements such as whole-body movements, kicking, and stretching subject the developing skeleton to stresses, strains and hydrostatic pressure. Animal studies have shown that limiting fetal movements by inhibiting or immobilising muscle activity leads to altered activity of developmental regulatory genes and skeletal abnormalities such as reduced rudiment length and bone formation, distorted spinal curvature, and abnormal joint cavitation and morphogenesis, highlighting the importance of these forces for normal development (Brunt et al, 2015;Kahn et al, 2009;Levillain et al, 2019;Nowlan et al, 2010a;Nowlan et al, 2010b;Roddy et al, 2011;Rolfe et al, 2013;Sotiriou et al, 2019).…”
Section: Loading Effects On In Vitro Skeletogenesismentioning
confidence: 99%
“…introduction Healthy skeletal development depends on physiological ranges of biomechanical stimuli, evident by the range of musculoskeletal conditions associated with reduced fetal movement reported in clinical cases and in in vivo animal immobilisation models (reviewed in Nowlan, 2015). However, the understanding of how type and quantity of mechanical stimulation directs cartilage and bone www.ecmjournal.org N Khatib et al…”
mentioning
confidence: 99%
“…In order to increase the production of extracelular matrix and mechanical properties of the cultured tissues, mechanical stimulation in bioreactors has provided good results. Various experimental studies in bioreactors have shown that the application of cyclic unconfined compression at moderate strains (2-15%) and frequencies (0.01-3Hz) stimulates the production of collagen and proteoglycans and increases the mechanical properties of the constructs (Lee and Bader 1997;Hung et al 2004;Kisiday et al 2004;Tsuang et al 2008;Lin et al 2014). Computational modeling techniques are useful to establish protocols for mechanical stimulationof tissueengineered cartilage, as well as to provide further insights on outputs not easily measurable experimentally.…”
Section: Introductionmentioning
confidence: 99%